2014
DOI: 10.1177/0269216314526766
|View full text |Cite
|
Sign up to set email alerts
|

Quality end-of-life care for dementia: What have family carers told us so far? A narrative synthesis

Abstract: Background:People with dementia do not always receive good quality end-of-life care, with undertreated pain, aggressive medical interventions and limited access to hospice care being common. Family carers often provide the majority of informal care for people with dementia, therefore may be best placed to comment on quality of care.Aim:We explored what quality end-of-life care for dementia is from the perspective of family carers.Design:A review of qualitative evidence taking a systematic approach using a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 58 publications
(154 reference statements)
2
80
0
2
Order By: Relevance
“…In this role the “best interests” principle of the Mental Capacity Act (Department for Constitutional Affairs, ) highlights that a decision made must be done in the relative's best interest, recognizing all aspects of financial and personal welfare, but also healthcare decisions and actions. Following their narrative analysis of families’ perspectives of dementia end‐of‐life care, Davies, Maio, Rait, and Iliffe () highlighted that there remains limited research on carers’ experiences at this stage. They recommended that more information is needed from carers to provide a greater in‐depth understanding.…”
Section: Introductionmentioning
confidence: 99%
“…In this role the “best interests” principle of the Mental Capacity Act (Department for Constitutional Affairs, ) highlights that a decision made must be done in the relative's best interest, recognizing all aspects of financial and personal welfare, but also healthcare decisions and actions. Following their narrative analysis of families’ perspectives of dementia end‐of‐life care, Davies, Maio, Rait, and Iliffe () highlighted that there remains limited research on carers’ experiences at this stage. They recommended that more information is needed from carers to provide a greater in‐depth understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing patients with dementia and patients with cancer have found that patients with dementia were prescribed lower doses of opioids than patients with cancer with similar pain scores, and opioids were more likely to be prescribed as monotherapy in patients with dementia, which is inconsistent with industry recommendations. 9,12 …”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in this study, not all will have such a supportive view and opinions will vary. As shown in previous reviews of attitudes towards end-of-life care in dementia, carers’ views in particular may change and span a spectrum of beliefs 4. Caution would also need to be taken of any other comorbid psychological disorders such as depression, which may compound an individual's desire for assisted dying 5…”
Section: Commentarymentioning
confidence: 99%